Determinan Ketimpangan Pembangunan di Indonesia - Ferdian, Ari; Azhar, Zul; Riani, Novya Zulva (Universitas Negeri Padang, 2024)
The purpose of this study is to analyze the influence of the rate of economic growth, human development index (HDI), foreign investment (PMA) and labor force on development inequality in Indonesia. This research uses panel data from 2017 to 2022 in 34 provinces in Indonesia sourced from the Central Statistics Agency (BPS). By using a panel data regression model, this research reveals that the rate of economic growth and foreign investment (PMA) have a positive and significant effect on development inequality. The human development index (HDI) has a negative and insignificant effect on development inequality and the workforce has a positive and insignificant effect on development inequality.